A associação entre experiências adversas na infância e transtorno de personalidade borderline - Almeida, Fernando José Porto (Universidade Federal de São Carlos, 2025)
Child development is a sequence of critical events that are highly sensitive to extreme stressors. In this context, adverse childhood experiences (ACEs) create a toxic developmental environment potentially associated with severe and lasting impairments in an individual’s functioning. Among ACEs, emotional and physical abuse and neglect, as well as sexual violence, are significantly related to the development of personality disorders, particularly borderline personality disorder (BPD). Characterized by intense emotional instability, significant functional impairments, and a high risk of suicide, BPD is closely linked to childhood trauma. This study aimed to investigate the association between adverse childhood experiences and borderline personality disorder, based on the hypothesis that ACEs contribute to the development of BPD and are closely related. The study included 141 participants with a mean age of 27 years, predominantly White female university students. Participants were divided into two groups: (1) individuals with suspected or diagnosed BPD and (2) individuals without suspicion or diagnosis. They completed an online questionnaire comprising the Brazilian version of the Adverse Childhood Experiences International Questionnaire, the Big Five Inventory 2 - Short Version (BFI-2-S), and the Dimensional Clinical Personality Inventory - Borderline Personality Disorder (IDCP-BPD). The data were organized and analyzed using descriptive and inferential statistics (correlation). The results indicate significant associations between ACEs and BPD, showing that higher total ACE scores correspond to a greater likelihood of having experienced physical abuse, emotional abuse, sexual abuse, emotional neglect, and bullying, or of having witnessed violence within the family or community. These individuals also exhibited more pronounced borderline personality traits. Similarly, Group 1 had higher ACE scores, particularly in the domains of physical abuse, emotional abuse, sexual abuse, emotional neglect, having an incarcerated family member, family violence, the presence of one or no parents, parental separation or divorce, bullying, community violence, collective violence, and total ACE score. Additionally, this group displayed significantly higher scores in factors related to pathological personality traits characteristic of BPD.
Adverse childhood experiences and borderline personality disorder association
Keywords: Transtorno de personalidade-borderline; Experiências adversas na infância; Traços de personalidade; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA